Exploratory factor analysis on Hurtt’s professional skepticism scale:a Malaysian perspective - Sayed Alwee Hussnie Sayed Hussin,; Takiah Mohd Iskandar, (FEP, 2013)
In auditing, professional skepticism refers to an attitude that requires ongoing questioning and critical assessment of evidence. An auditor needs to exercise professional skepticism to obtain sufficient and appropriate audit evidence to determine whether financial statements are free from material misstatements due to errors or frauds. Hurtt (2010) developed a professional skepticism scale to measure the level of an auditor’s skepticism. However, the exercise of professional skepticism among auditors is very subjective and difficult to measure. The validity of the Hurtt skepticism scale in the context of different countries requires further examination. A factor analysis study is conducted to validate the suitability of the instrument based on Malaysian data. The results indicate that only five of the Hurtt (2010) skepticism traits are relevant in determining professional skepticism in the Malaysian environment. The suspension of judgment trait seems to be irrelevant since respondents feel that this trait requires more time to make audit decisions and may delay audit work. Malaysian auditors are not likely to possess such a trait because they are burdened with numerous audit tasks that must be completed by a deadline. The results suggest that variances may exist across different countries due to differences in environment.